PENGARUH PEMBERIAN JAMU TRADISIONAL DALAM AIR MINUM TERHADAP PERFORMA BROILER - Firdaus, Janu; Kurtini, Tintin; Riyanti, Rr (JURUSAN PETERNAKAN, FAKULTAS PERTANIAN, UNIVERSITAS LAMPUNG, 2017)
The purpose of this research was to: 1) know the effect of Curcuma domestica extract, leaf mixed boiling of Psidium guajava L and Piper betle Linn in drinking water on broiler performance; 2) know the optimal supply of Curcuma domestica extract, boiling of green Piper betle Linn leaf and Psidium guajava L leaf in drinking water was better on broiler performance. The research was conducted in 2th October to 30th October, 2015 as long as 30 days in Janu Farm, Serdang Village, Tanjung Bintang Subdistrict, South of Lampung Regency. The method of this research used expermental technique with completely randomized design (CRD), consist of 3 treatments and 6 replications. The treatments were: 1) P0: well water; 2) P1: Curcuma domestica extract and; 3) P2: the leaf boiling of Psidium guajava L and Piper betle Linn with comparison of 50% : 50%. Ninethy DOC broiler Lohmann strain were long as 28 days. The results showed that: (1) Curcuma domestica extract (P1) and mixed of Psidium guajava L and Piper betle Linn leaf extract (P2) in drinking water were not significantly different (P>0,05) of drinking water consumption, body weight, and feed cunvertion ratio but significantly on feed consumption. (2) The mixed of Psidium guajava L and Piper betle Linn leaf extract (P2) in drinking water of broiler showed best performance on feed consumption ratio. Keyword: Broiler, Traditional Herbal, Performance, air